Collection and consumption of wild forest fruits in rural Zambia - Ickowitz, A.; Bwembelo, L.; Mulani, A.; Siamutondo, A.L.M.; Banda, P.; Gumbo, D.J.; Moombe, K.B.; Steel, E.A. (Center for International Forestry Research, 2021)
We report results from a study carried out in Zambia, in which 209 households were surveyed across all of the country’s agroecological zones. Based on the results of this survey and other nationally available data, we estimate that, for surveyed households, wild fruits collected from forests contribute approximately 80% of total fruit intake.